Child Protection Systems in Indonesia and Malaysia: Between Theories and Practices (Universitas Negeri Semarang, 2022)
Child protection is one of the most important things in life, because basically a child cannot protect himself. Starting from actions or treatments that can result in psychological, physical and social losses, so that one of the steps in overcoming this is to ensure protection. The government's effort in tackling this problem is to create a statutory regulation regarding the protection and needs of children's rights which becomes a reference for the effectiveness of efforts in child protection issues. Because the law discusses how we should treat children so that they are prosperous and protected and their needs and rights are fulfilled. In an effort to understand it further, this journal was created to compare the concept or basis of child protection from Indonesia and Malaysia. The method in making this journal is to collect other research journals and also normative legal comparisons, which can be sourced from the Convention on the Rights of the Child and the Law on Child Protection in Indonesia and Malaysia.